Frequent Skin Injuries in Neonates from Various Skin Injuries Monitoring Instruments: A Systematic Review - Tanty Harjati; Yeni Rustina; Dessie Wanda (STIKep PPNI Jawa Barat, 2023)
Aims: Maintenance of skin and tissue integrity is one of the main focuses of various health care facilities throughout the world so that the implementation of effective prevention of skin trauma requires a protocol for early identification of at-risk patients in prevention of skin trauma. Objective: Knowing the effektiveness of the SRAMT instrument compared to other skin trauma monitoring instruments for monitoring neonatal skin trauma. Method: This research method is in the form of systematic review, database search is done through proquest, SAGE Journal, Sciencedirect, Clinicalkey Nursing and manual research. There were eight journal articles that met the inclusion criteria. Based on the article it was concluded that the instrument had gone through validity, reliability, interrater tests and correlation coefficients so that it was suitable for use in pediatric and neonatal patients. Result: There were seven journal articles that met the inclusion criteria. The most common type of skin injury are caused by the use of an indwelling vascular catheter and medical devices. The most common locations for skin injury are the nasal septum and the head area, including the face and scalp. Compared to other skin injury monitoring instruments, the SRAMT subscale is more comprehensive by having three skin trauma risk assessment sections, including skin trauma risk categories, management guidelines based on skin injury risk categories and prevention that can be carried out based on the type of skin injury that occurred. This guide is very important to reduce the risk of skin injury in neonates and provide uniformity in nursing care provided by nurses.